ILOKUSI TUTURAN TOKOH UTAMA DALAM KOMIK TIGA MANULA JALAN-JALAN KE SINGAPURA KARYA BENNY RACHMADI - Chan, Dwi Mutia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2019)
The aim of this study: (1) describe the type of illocutionary speech acts used the main character in the comic discourse Three Seniors Streets Benny Rachmadi Singapore to work, (2) describe the function of illocutionary speech acts used the main character in the comic discourse Seniors Three Roads to the work of Benny Singapore Rachmadi, (3) describe the dominant illocutionary speech acts used the main character in the comic discourse Three Seniors Streets Benny Rachmadi Singapore to work. This research is a qualitative research method in this study deskriptif.Data main character in the form of narrative discourse Seniors comic Three Roads to Singapore Work Rachmadiyang Benny containing illocutionary speech acts. Data collection techniques used in this study is the technique of note, which is a technique used by researchers dealing with the use of written language. Based on the research results, it was concluded the following. First, the type of illocutionary speech acts used the main character in the comic discourse Seniors Three Roads to the work of Benny Rachmadi Singapore found 28 utterances. Representative speech acts found 13 utterances, 11 utterances directive, and the declaration of 4 utterances. Second, the function of illocutionary speech acts used the main character in the comic discourse Seniors Three Roads to Singapore by Benny Rachmadi found 12 utterances. Competitive speech act functions found 3 tuturanmenyenangkan 3 utterances, working 3 utterances, and found 3 contradicts speech. Third, the type of illocutionary speech acts used the dominant discourse of the main character in the comic Three Seniors Streets to Singapore by Benny Rachmadi is representative speech act, illocutionary speech acts and functions of the dominant discourse used the main character in the comic Three Seniors Streets to Singapore by Benny Rachmadi is no dominant speech acts.